ANALISIS PENGARUH KUALITAS PELAYANAN TERHADA KEPUASAN KONSUMEN PADA BOLLY DEPARTEMEN STORE KOTA BIMA - Fakrin Fakrin; Intisari Haryanti (Pusat Riset dan Publikasi, 2022)
This study aims to determine the analysis of the influence of service quality on customer satisfaction at the bolly department store of the city of Bima population and the sample of this study is to use the unknowns population formula whose population is not known to determine the sample. The number of samples in this study is 96.04 or rounded up to 96 respondents in accordance with the criteria that have been set. The results of this study are partially the effect of service quality on customer satisfaction at the bolly department store in the city of Bima. Simultaneously or simultaneously the effect of service quality on customer satisfaction at the bolly department store Bima city. The correlation value (r) generated is 0.203. So it can be concluded that there is a very low relationship between the independent variable and the dependent variable. While the value of r square is 0.041. This shows that the overall service quality variable has an influence of 0.041% on consumer satisfaction, while the remaining 95.9% is influenced by other variables not examined in this study. Keywords: service quality and customer satisfaction.